MITIGATION OF ZAKAT INSTITUTION RISKS IN POVERTY ALLEVIATION BASED ON ZAKAT CORE PRINCIPLES - Ely Windarti Hastuti; Haura Nailul Hidayah (JSE: Jurnal Sharia Economica, 2026)
Efforts to optimize zakat in Indonesia, zakat management institutions that have been recognized by the government consist of the National Zakat Agency (BAZNAS) and the Zakat Management Institution (LAZ). The aim is to analyze the implementation and risk reduction in zakat manangement institutions in terms of fund collection, distribution, and reporting. This study is based on the theory of risk management in non-profit organizations, which emphasizes operational risk control to improve accountability and public trust. The method used is qualitative with primary and secondary data sources. The focus of this study is the branch heads and employees of three zakat management institutions in Surakarta; LAZ Yatim Mandiri Surakarta, LAZ Nurul Hayat Surakarta, and LAZ DT Peduli Surakarta. The results show that zakat institutions in Surakarta have implemented risk mitigation strategies by improving internal controls in the processes of fundraising, distribution, and reporting of funds. The implementation of ZCP numbers 10, 16, and 18 plays an important role in mitigating the risks of zakat management. The results indicate that zakat management policies need to be strengthened and also serve as a basis for strengthening national zakat governance policies.